Risk Factors for Abnormal Cervical Cytology in Pregnant Women Attending the High-Risk Obstetrics Clinic at the University Hospital in San Juan, Puerto Rico - Seda, Jaffet; Avellanet, Yaniris; Roca, Fernando J.; Hernández, Eduardo; Umpierre, Sharee A.; Romaguera, Josefina (Puerto Rico Health Sciences Journal, 2011)
Objective: Approximately 30% of women diagnosed with cervical cancer are in their childbearing years, and 5-8% of pregnant women seeking prenatal care are found to have an abnormal Papanicolaou smear. Prenatal visits are an excellent opportunity for cervical cytology testing and patient education because of close follow-up. The objective of this study is to examine the overall prevalence of cervical dysplasia and associated risk factors in pregnant women aged 15 to 30 years attending the highrisk obstetrics clinics at the University Hospital in San Juan, Puerto Rico between December 2005 and May 2007. Methods: We performed a systematic review of 237 prenatal charts from patients attending the high-risk obstetrics clinics at the University Hospital in San Juan. The variables studied were age, place of birth, gestational age at first visit, gravidity, age at first coitus, number of sexual partners, tobacco use, Papanicolaou smear results, and cervical gonorrhea and Chlamydia test results. The relationship between cervical cytology results and the aforementioned variables was statistically assessed. Results: Abnormal cervical cytology was found in 16 (6.8%) of the patients. Of these, 75% were atypical squamous cells of unknown significance (ASCUS), 19% low-grade squamous intraepithelial lesion (LGSIL), and 6% high-grade squamous intraepithelial lesion (HGSIL). Gravidity > 3 was observed in 16.5% of the patients, and 48.7% were in their second trimester of gestation. Their first coitus was at age 17 or earlier (66.5%), and 78% had between 1 and 3 sexual partners. Having a positive Chlamydia test was significantly (p < 0.05) associated with the risk of having an abnormal cervical cytology. Other variables such as gravidity, age at first coitus, number of sexual partners, and tobacco use were not statistically associated with an abnormal cervical cytology test. Conclusion: The overall prevalence of cervical dysplasia among pregnant women who attend the high-risk obstetrics clinic at the University Hospital in San Juan, Puerto Rico is similar to what has been reported elsewhere. Among all variables studied, only a positive Chlamydia test was found to be associated with an abnormal cervical cytology test. Given the high number of women seeking prenatal care and the close follow-up provided during this period, prenatal care is an excellent opportunity for cervical cytology testing and patient education.